A Comparative Exploration of Science (Physics) Education Practices in India, China, and Indonesia - Rostika, Rince Aida Rostika; Hermalia Putri; Ersa Dwi Anggraini; Doesti; Irwan Koto (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to examine a comparative analysis of physics education and learning systems in three countries: Indonesia, India, and China. The primary focus is to identify similarities and differences in pedagogical approaches, curriculum structure, and the integration of technology in physics instruction. The research employs a literature review method using a descriptive qualitative approach. The analysis reveals that all three countries place significant emphasis on educational development, particularly in science and physics. China stands out with its highly centralized and competitive education system, as well as its advanced use of technology in physics learning, such as augmented reality. India emphasizes the integration of physics education with local culture and the implementation of project-based learning. Meanwhile, Indonesia is undergoing a transition toward a more contextual and technology-based learning system, although it still faces challenges in terms of equitable access to facilities and teacher training. The study concludes that despite the unique challenges faced by each country, physics education can be enhanced through the integration of contextual approaches, technology, and teacher capacity building.